The Mitochondrial Genome of the Phytopathogenic Fungus Bipolaris sorokiniana and the Utility of Mitochondrial Genome to Infer Phylogeny of Dothideomycetes - Song, Nan; Geng, Yuehua; Li, Xinghao (Frontiers in Microbiology, 2020)
A number of species in Bipolaris are important plant pathogens. Due to a limited number of synapomorphic characters, it is difficult to perform species identification and to estimate phylogeny of Bipolaris based solely on morphology. In this study, we sequenced the complete mitochondrial genome of Bipolaris sorokiniana, and presented the detailed annotation of the genome. The B. sorokiniana mitochondrial genome is 137,775 bp long, and contains two ribosomal RNA genes, 12 core protein-coding genes, 38 tRNA genes. In addition, two ribosomal protein genes (rps3 gene and rps5 gene) and the fungal mitochondrial RNase P gene (rnpB) are identified. The large genome size is mostly determined by the presence of numerous intronic and intergenic regions. A total of 28 introns are inserted in eight core protein-coding genes. Together with the published mitochondrial genome sequences, we conducted a preliminary phylogenetic inference of Dothideomycetes under various datasets and substitution models. The monophyly of Capnodiales, Botryosphaeriales and Pleosporales are consistently supported in all analyses. The Venturiaceae forms an independent lineage, with a distant phylogenetic relationship to Pleosporales. At the family level, the Mycosphaerellaceae, Botryosphaeriaceae. Phaeosphaeriaceae, and Pleosporaceae are recognized in the majority of trees.